Factors Associated with Vancomycin-Resistant Enterococcus (VRE) Infection among Hospitalized Patients at Samutprakan Hospital - ลี้ทอง, พรวิมล (Journal of Health Science of Thailand, 2024)
This matched case-control study aims were to describe the epidemiology of Vancomycin Resistant Enterococci (VRE) and identify factors associated with infection of VRE among hospitalized patients at Samutprakan Hospital between January 1, 2022 and December 31, 2023. The case were 86 patients infected with VRE and the control case 172 patients with Vancomycin Sensitivity Enterococcus (VSE). Both groups were matched by sex, age and same type of specimen in the same month. Data were collected retrospectively from hospital electronic medical record database and culture results. Condition logistic regression was used to identify risk factors associated with VRE infection. Odds ratio and 95% confidence interval were calculated and p-value less than 0.05 to indicated statistical significance.